A Conceptual Model Using The Elliptic Curve Diffie–Hellman With An Artificial Neural Network Over Cloud Computing - Jaber, Aws Naser; Mohamad Fadli, Zolkipli; Othman, Hanshal (Universiti Malaysia Pahang, 2016)
Cryptography makes taking a cipher and duplicating the original plain content difficult without the comparing key. With all-around outlined cryptography, messages are scrambled in a manner that savage power assaults against the calculation or the key are everything except unthinkable. A solid cryptography obtains its security from the utilization of staggeringly long keys and encryption calculations that are impervious to different types of assault. Neural net application represents the following advancement in great cryptography. This study manages the utilization of a neural system in cryptography, particularly, the configuration of a neural system that can be commonsense use in cryptography. This focus also incorporates an experimental demonstration